Skin mucus proteome analysis reveals disease-resistant biomarker signatures in hybrid grouper Epinephelus fuscoguttatus a x Epinephelus lanceolatus a‚ against Vibrio alginolyticus - Nurhikmah; Christianus, Annie; Wan Solahudin, Wan Mohd Syazwan; Lau, Benjamin Yii Chung; Ismail, Intan Safinar; Fei, Low Chen (MDPI, 2022)
Fish skin mucus is the first line of defense that provides physical and chemical barriers against pathogens and toxins. The mucus is produced continuously and sloughed off regularly from the skin to defend against infections through the skin. However, the molecular properties of the mucus content that prevent pathogen invasion are yet to be fully understood. In this study, a proteomic approach using liquid chromatography–mass spectrometry (LCMS) was applied to explore the changes in the mucus protein content of resistant and susceptible groupers in response to Vibrio alginolyticus. The Vibrio-resistant groupers showed no observable clinical sign of infection after the immersion challenge, while the Vibrio-susceptible groupers presented either hemorrhagic- or non-hemorrhagic ulceration of the skin. A comparative proteome analysis on the mucus samples yielded 1488 identified proteins. The immune-related proteins, namely Cystatin B, Complement Component C6, Complement factor 1, Allograft inflammatory factor 1, Deleted in malignant brain tumors protein, MHC class 1 and Annexin A1, that were significantly abundant in the resistant group responded to V. alginolyticus infection. Interestingly, there was an expression of immune-related proteins that possibly could be the non-invasive biomarkers, namely 3-hydroxybutyrate dehydrogenase type 2 and L-rhamnose-binding lectin SML.